Biodegradable highly porous interconnected poly(ε‐caprolactone)/poly(L‐lactide‐co‐ε‐caprolactone) scaffolds by supercritical foaming for small‐diameter vascular tissue engineering. (12th October 2021) - Cao, Yongjun; Jiang, Jing; Jiang, Yufan; Li, Zihui; Hou, Jianhua; Li, Qian
Abstract: Biodegradable ϕ 4 mm tubular porous poly(ε‐caprolactone)/poly(L‐lactide‐co‐ε‐caprolactone) (PCL/PLCL) scaffolds are fabricated successfully via one‐step microcellular supercritical carbon dioxide foaming process. The effect of blending ratio on the rheology, pore structures, mechanical property, wettability, and biocompatibility of PCL/PLCL blends tubular scaffold are reported. Rheological results show that PCL matrix and PLCL dispersed phase has good compatibility. The melt strength of PCL can be enhanced obviously by adding PLCL. With an increase of PLCL content from 10 to 30 wt%, the pore size increases from 7.6 to 24.9 μm due to the homogeneous nucleation effect. The maximum open‐cell content can reach 77% for PCL/PLCL foamed sample. Cyclical tensile and compliance tests show that few content of dispersed PLCL (10–20 wt%) improves the flexibility and recoverability. Cell viability results demonstrate that human umbilical vein endothelial cells (HUVECs) cultured on all PCL/PLCL porous scaffolds exhibit a typical spindle‐like cell morphology. Moreover, HUVECs have a higher density and spreading areas on surface of 10% PLCL scaffold. The results gathered in this paper may open a new perspective for the fabrication of small‐diameter vascular tissue engineering scaffold.